Ferromagnetism With High Curie Temperature of Cu Doped LiMgN New Dilute Magnetic Semiconductors - Deng, Junquan; Yang, Wuqing; Hu, Aiyuan; Yu, Peng; Cui, Yuting; Ding, Shoubing; Wu, Zhimin (Frontiers in Materials, 2021)
New diluted magnetic semiconductors represented by Li(Zn,Mn)As with decoupled charge and spin doping have received much attention due to their potential applications for spintronics. However, their low Curie temperature seriously restricts the wide application of these spintronic devices. In this work, the electronic structures, ferromagnetic properties, formation energy, and Curie temperature of Cu doped LiMgN and the corresponding Li deficient system are calculated by using the first principles method based on density functional theory, combined with Heisenberg model in the Mean-Field Approximation. We find that the Cu doped systems have high temperature ferromagnetism, the highest Curie temperature is up to 573K, much higher than the room temperature. Li(Mg0.875Cu0.125)N is a half metallic ferromagnet and its net magnetic moments are 2.0 μв. When Li is deficient, the half metallic ferromagnetism becomes stronger, the magnetic moments increase to 3.0 μв. The bonding and differential charge density indicate that the half metallic ferromagnetism can be mainly attributed to the strong hybridization between N 2p and doped Cu 3d orbitals. The results show that Cu doped LiMgN is a kind of ideal new dilute magnetic semiconductor that will benefit potential spintronics applications.